Massive Adherent Placenta, Placenta Percreta - Yuliantara, Eric Edwin; Anggraini, Nutria Widya Purna; Prisasanti, Dympna Prameilita (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background: Adherent placentas including placenta accreta, increta and percreta are conditions where there is abnormal implanta